Alguém possa me ajudar ?
Anexos:
![](https://pt-static.z-dn.net/files/db5/ef9bdfb413abf5366631811fd8fb5a9e.jpg)
Soluções para a tarefa
Respondido por
1
É só calcular. Substitui x na S(x) por -1
S(-1)= (4/5)^-1
= 5/4
g(-3)= (5/4)^-3
= 4^3/5^3
= 64/125
Agora, subtrai
5/4-64/125= (5.125)/(4.125)-(64.4)/(125.4)
625/500-256/500= 625-256/500
369/500
Logo, a afirmação 1 é falsa
S(-1)= (4/5)^-1
= 5/4
g(-3)= (5/4)^-3
= 4^3/5^3
= 64/125
Agora, subtrai
5/4-64/125= (5.125)/(4.125)-(64.4)/(125.4)
625/500-256/500= 625-256/500
369/500
Logo, a afirmação 1 é falsa
ryanvive:
Muito obrigado
Perguntas interessantes
Português,
11 meses atrás
História,
11 meses atrás
Matemática,
11 meses atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás